Excuses in Exile - Kaye, Anders (2015)
Suppose that I have intentionally killed another person and that I have done so without any justification. At first glance, it appears that I am guilty of murder, a very serious crime. Since I am guilty of this very serious crime, the state may inflict a very serious punishment on me—at least many years in prison, if not my whole life or the death penalty. But suppose that one of the following is also true in my case: (A) At the time that I killed my victim, I suffered from a mental disease and, as a result, lacked the substantial capacity to appreciate the wrongfulness of my conduct. (B) Throughout my childhood and into my adolescent years, my father physically and sexually abused me, leaving me significantly more prone to violence than I would otherwise have been. Both A and B are ethically and interpersonally important facts. Both are likely to inspire some combination of sympathy, empathy, and compassion. Both suggest that my story is not just the story of a murderer and that there is a complicated explanation for my crime